Debolezze e diritti: la riforma psichiatrica nel riscatto della soggettività esclusa (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The market for aesthetic medicine is constantly growing and, except “reconstructive” surgery that responds exclusively to the need to improve the appearance, it presents a number of legal, but also strictly ethical and professional questions. The aim of the authors is, through a literature review, to discuss whether it can still be possible to deal with an idea of aesthetic medicine extraneous to the concept of disease and, therefore, to re-evaluate the position of the aesthetic surgeon with its authoritative professional dignity.
Keywords: Psychiatric reform; asylum; self-determination; mental health; Franco Basaglia